Applying Online Gamification as the Media in Online Learning for Enhancing Learners’ Vocabulary. - Ella Aprilia Tiana; Khoirul Anwar; Ulfah Marifah (Jetlal, 2022)
(Lynn & Holderness, 2013) acknowledged that vocabulary is an important part of student education. Without learning vocabulary, students can lose the ability to read and understand. This study aimed to find out the significant differences in applying Kahoot, Quizziz and Google form as the media of exercise in online learning for enhancing learner's vocabulary. The design of this study was quasi-experimental. The population of this study was the 8th grade of junior high school 17 Gresik. There were 2 Experimental groups and 1 control group consisted of 32 students each. The instruments of the study were a pre-test and a post-test of vocabulary mastery and using an online media called Kahoot, Quizizz and Google form. The data were analyzed using SPSS 16.0. The finding showed that there were significant differences by using Kahoot and Quizizz as media of exercise to the students' vocabulary, while there was no significant different using google form. Further testing using Anova showed that there were no any significant differences among those 3 media.